Effects of Self-Efficacy in the Life of Student Academic Procrastination - Yuniva Dwi Indah Lestari; Ananta Yudiarso (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
In psychology, the phenomenon of procrastination is called procrastination. Procrastination or procrastinating work that occurs in the academic area is commonly called academic procrastination. Academic procrastination is a frequent procrastinatory behavior in schools and universities that results in negative student performance. Procrastination behavior causes negative effects of anxiety or stress and rarely has a positive behavioral impact. The effect of procrastination behavior is the emergence of anxiety about fear of failure and decreased self-motivation. Another impact of procrastination behavior is lower academic self-esteem and lower learning effectiveness. Several studies have shown that there is a correlation between self-efficacy and academic procrastination. Therefore, this meta-analysis study serves to test the effect of size self-efficacy on academic procrastination.  This study used 15 journals with a total of 2580 respondents. All of these journals describe the results of research with a negative correlation between self-efficacy and academic procrastination. This study also obtained random effect size results of -0.08 (95% CI= -0.38 to 0.22) with I2 (inconcruency) = 98.25% and egger regression of P=0.584. Calculations using moderates in the categories of self-efficacy measurement tools, academic procrastination measuring instruments and research areas showed that there was no publication bias. Based on the results of the meta-analysis analysis, it can be seen that self-efficacy is only slightly correlated with academic procrastination, which means the low influence between self-efficacy and academic procrastination. Therefore, it is expected that the research will contribute to further researchers in further studying the problem of academic procrastination. Dalam dunia psikologi, fenomena menunda-nunda disebut dengan prokrastinasi. Prokrastinasi atau menunda-nunda pekerjaan yang terjadi pada area akademik biasa disebut dengan prokrastinasi akademik. Prokrastinasi akademik merupakan perilaku penundaan yang sering terjadi di sekolah dan di Universitas yang mengakibatkan hal negatif pada kinerja siswa. Perilaku prokrastinasi menimbulkan dampak negatif yakni kecemasan atau stres dan jarang memberikan dampak perilaku positif. Pengaruh dari perilaku prokrastinasi tersebut adalah timbulnya kecemasan terhadap ketakutan akan kegagalan dan motivasi dalam diri yang menurun. Dampak lain dari perilaku prokrastinasi adalah harga diri akademik yang lebih rendah dan efektivitas belajar yang lebih rendah. Beberapa penelitian telah menunjukkan bahwa terdapat korelasi antara self-efficacy dan prokrastinasi akademik. Maka dari hal itu studi meta analisis ini  berfungsi untuk menguji tentang effect size self-efficacy terhadap prokrastinasi akademik.  Studi ini memakai 15 jurnal dengan jumlah responden 2580 orang. Ke semua jurnal tersebut memaparkan tentang hasil penelitian dengan korelasi negatif antara self-efficacy dan prokrastinasi akademik. Penelitian ini juga mendapatkan hasil random effect  size sebesar -0,08 ( 95% CI= -0,38 sampai 0,22) dengan I2 (inconcruency) = 98,25%  dan egger regression sebesar P=0,584. Perhitungan menggunakan moderator kategori alat ukur self-efficacy, alat ukur prokrastinasi akademik dan wilayah penelitian menunjukkan bahwa tidak terdapat bias publikasi. Berdasarkan hasil analisa meta analisis dapat diketahui bahwa self-efficacy hanya sedikit berkorelasi dengan prokrastinasi akademik, yang artinya rendahnya pengaruh antara  self-efficacy terhadap prokrastinasi akademik. Oleh sebab itu diharapkan dari penelitian memberikan sumbangsih terhadap para peneliti selanjutnya dalam mengkaji lebih lanjut mengenai permasalahan prokrastinasi akademik.